Effect of saliva isolation and intraoral light levels on performance of intraoral scanners - Camcı, Hasan; Salmanpour, Farhad (American journal of orthodontics and dentofacial orthopedics, 2020)
The use of digital models in orthodontics is becoming increasingly widespread. This study aimed to evaluate the accuracy and performance of digital intraoral scanning under 4 different intraoral environmental conditions. Four digital models were acquired with TRIOS intraoral scanner (3Shape, Copenhagen, Denmark) for 50 subjects. A total of 200 digital models were divided into 4 groups as follows: daylight and saliva (group 1), daylight with saliva isolation (group 2), reflector light and saliva (group 3), and relatively dark oral environment and saliva (group 4). The 4 digital models were superimposed, and the edges of the models were trimmed to create common boundaries (Geomagic Control X; 3D Systems, Rock Hill, SC). Group 2 models were used as a reference and superimposed separately with the models of the other 3 groups. Deviations between corresponding models were compared as means of negative deviation, means of positive deviation, in total area, out total area, positively positioned areas, and negatively positioned areas. In addition, all groups were compared in terms of scanning time, the total number of images, and the mesiodistal width of teeth. Overlapping of group 1 with the reference model (group 2), a surface deviation of 13.1% (out total area) was observed. This analysis revealed that a 13% deviation was caused by the presence of saliva alone. This rate was 12.6% in group 3 and 15.5% in group 4, respectively. The values for means of negative deviation were −55 μ in group 1,−63 μ in group 3, and −68 μ in group 4. Means of positive deviation values were distributed among groups as follows: 68 μ in group 1, 69 μ in group 3, and 78 μ in group 4. The total number of images was observed, at least in group 4. The intraoral scanner performance was affected by different environmental conditions, and that caused variations on the surface of digital models. However, the performance of the intraoral scanner was independent of the scanning time and mesiodistal width of the teeth. •The use of digital models in orthodontics has become increasingly widespread.•Light levels and saliva affect the performance of intraoral scanners.•Scanning time is not affected by saliva or light level.•Some environmental conditions cause variations on the surface of digital models.